Analisis SWOT Strategi Pelayanan Gereja Masehi Advent Hari Ketujuh Jemaat Banjarmasin Di Masa Pandemi Covid-19 - Janes Sinaga; Juita Lusiana Sinambela (JUITAK : Jurnal Ilmiah Teologi dan Pendidikan Kristen, 2023)
This research aims to explore and analyze the service strategy of the Seventh-day Adventist Church (GMAHK) in the Banjarmasin Congregation. Using a qualitative approach, this research explores various aspects of ministry strategies, including teaching, social service, and community involvement, to understand their impact on congregational growth and relationships with the community. The research population includes members of the GMAHK Banjarmasin congregation who are involved in church services. Data was collected through direct observation, interviews with church leaders, congregation members, and volunteers, as well as analysis of church documents. A thematic analysis approach is used to identify patterns and meaning related to service strategies. It is hoped that the results of this research will provide new insights that can increase the effectiveness of church services, especially in the context of the local culture and environment of the Banjarmasin congregation. By focusing on developing relevant and significant services, this research has the potential to make a positive contribution to the congregation's spiritual growth and positive interactions with the surrounding community.